Estimate of background baseline and upper limit on the chiral magnetic effect in isobar collisions at √sNN=200 GeV at the BNL Relativistic Heavy Ion Collider - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2024)
For the search of the chiral magnetic effect (CME), STAR previously presented the results from isobar collisions (9644Ru+9644Ru, 9640Zr+9640Zr) obtained through a blind analysis. The ratio of results in Ru+Ru to Zr+Zr collisions for the CME-sensitive charge-dependent azimuthal correlator (Δ⁢𝛾), normalized by elliptic anisotropy (𝑣2), was observed to be close to but systematically larger than the inverse multiplicity ratio. The background baseline for the isobar ratio, 𝑌=(Δ⁢𝛾/𝑣2)Ru(Δ⁢𝛾/𝑣2)Zr, is naively expected to be (1/𝑁)Ru(1/𝑁)Zr; however, genuine two- and three-particle correlations are expected to alter it. We estimate the contributions to 𝑌 from those correlations, utilizing both the isobar data and hijing simulations. After including those contributions, we arrive at a final background baseline for 𝑌, which is consistent with the isobar data. We extract an upper limit for the CME fraction in the Δ⁢𝛾 measurement of approximately 10% at a 95% confidence level on in isobar collisions at √𝑠𝑁⁢𝑁=200GeV, with an expected 15% difference in their squared magnetic fields.